Effect of Intravenous Lignocaine vs Placebo on Hemodynamic Responses during Direct Laryngoscopy - Nasir Ali Rahim Najjad, Salman Mohsin, Tooba Mughal, Zara Rizwan, Shakil Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the effect of placebo vs intravenous lignocaine pre-intubation on hemodynamic responses during direct laryngoscopy. Study design: Randomized control trial Place and duration of study: Department of Anaesthesia, Indus Hospital, Karachi from 1st March 2017 to 31st August 2017. Methodology: One hundred and twenty patients were included and divided into two groups. In one group, lignocaine arm (1.5mg/kg I/V lignocaine) was given while placebo arm was given (6ml normal saline pre-intubation) in group two. In both groups after arrival at the operation theatre, base-line parameters like the heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure was measured non-and later hemodynamic assessment was done before giving lignocaine, prior and post intubation and after 3,5 and 10 minutes of intubation. Results: Fifty six (46.15%) were male while 64 (53.85%) were females. No patients were found to have asthma, COPD, ischemic heart disease, TB, CHF, Cushing syndrome, phenochromcytoma, and drug allergy. No significant association was found between the two groups when comparing the gender, BMI, comorbids, ASA grade and Mallampati grade. The systolic blood pressure at 3,5 and 10 minutes was significant in the two groups, while diastolic was not significantly associated. The pulse rate at3 and 10 minutes was found to have a significant association while at 5 minutes was insignificant. MAP showed no significant association between the two groups. Conclusion: Hemodynamic stability is only affected in terms of systolic blood pressure, while other parameters are not significantly affected. Keywords: Lignocaine, Hymodynamic changes, Laryngoscopy